1967
DOI: 10.1111/j.1423-0410.1967.tb03368.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of External Version on Antenatal Immunization by the Rh Factor

Abstract: Summary The present study has shown that the routine practise of antenatal manipulations such as external version is associated with a significant increase in the frequency of episodes of Rh immunization not only among Rh negative mothers who were already immunized before the present pregnancy commenced but also among those not previously immunized. The findings would seem to indicate that the disruption of the placental circulation is enhanced by such procedures and the ultimate risk involved in intensifying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1972
1972
1982
1982

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Except for fetomaternal bleeds, no complications were observed. Vos (1967) found that 9 out of 113 rhesus negative mothers (8 per cent) in whom external version had been attempted developed rhesus antibodies, as against 33 out of 1007 (3 per cent) who had no external versions ; fetomaternal bleeds, as such, were not investigated in this study.…”
Section: Table I Fetal Red Cells Per Million Maternal Red Cells From mentioning
confidence: 65%
“…Except for fetomaternal bleeds, no complications were observed. Vos (1967) found that 9 out of 113 rhesus negative mothers (8 per cent) in whom external version had been attempted developed rhesus antibodies, as against 33 out of 1007 (3 per cent) who had no external versions ; fetomaternal bleeds, as such, were not investigated in this study.…”
Section: Table I Fetal Red Cells Per Million Maternal Red Cells From mentioning
confidence: 65%